Estudo da recria de novilhas de corte em pastagens cultivadas de verão - Glienke, Carine Lisete (2012)
Heifers rearing is a determinant step of efficiency in beef cattle production systems on pastures. Several experiments have tested alternative uses for tropical grasses to heifers rearing. In order to summarize results and making not visible relationships evident in these individual experiments an analysis was performed in a set of data from six experiments dealing with beef heifers rearing from 15 to 18 months of age on Pearl Millet (Pennisetum americanum), Alexandergrass (Urochloa plantaginea) and Coastcross (Cynodon dactylon) pastures. Canopy structure, herbage intake patterns, performance and body development of heifers were studied. Forage mass (3,000.4 kg DM/ha) and leaf blade mass (668.1 kg DM/ha) were similar between pastures while leaf blade: stem ratio of sward vertical strata was different. In Pearl Millet, higher forage allowance and canopy height were observed as well as less stems mass. The leaf blade allowance was higher in Pearl Millet (4.4%), intermediate in Alexandergrass (2.8%) and lower in Coastcross (1.8%). The daily intake of DM was lower in Coastcross (5.6 kg) compared to Alexandergrass (6.5 kg) and these values were similar to the value in Pearl Millet (6.1 kg). The bite mass and biting rate were similar in Pearl Millet and Alexandergrass. The main compensatory mechanism for smaller bite masses and reduced intake rates in Coastcross was increasing grazing time. The biting rate variations happened as a response to constraints imposed by the canopy architecture. Surface utilization on Alexandergrass and Coastcross was increased by the searching for leaf blades which influenced the increase of the number of feeding stations visited and displacement rate. Average daily gain was similar in Pearl Millet and Alexandegrass (0.864 kg) and less in Coastcross (0,610 kg). Daily weight gain per area was higher in Pearl Millet (8.1 kg/ha/day), which resulted in a higher production of total body weight (668.0 kg/ha). The body weight gain was mainly determined by forage mass and neutral detergent fiber in the three pastures. Body weight, body condition score, reproductive tract score, pelvic area and hip height were similar among heifers in the three grasses at 18 months of age. It suggests an adequate body development of heifers for mating at the end of pastures occupation, when the animals are at 18 months of age. To beef heifers rearing (from 14 to 18 months of age), Coastcross and Alexandergrass pastures are alternatives to Pearl Millet pasture.